Contribution of lianas to community‐level canopy transpiration in a warm‐temperate forest. (2nd May 2017) - Ichihashi, Ryuji; Chiu, Chen‐Wei; Komatsu, Hikaru; Kume, Tomonori; Shinohara, Yoshinori; Tateishi, Makiko; Tsuruta, Kenji; Otsuki, Kyoichi
Summary: Lianas (woody climbers) have a greater amount of leaves relative to basal area or standing biomass than trees, and very wide vessels that permit efficient water transport. These features suggest that lianas possibly consume proportionally more water through transpiration than trees. Despite their potential importance, researchers have made only limited attempts to evaluate effects of lianas on forest water dynamics. We conducted sap flow measurements for 1 year using a thermal dissipation method for four species each of lianas and trees in a liana‐rich, warm‐temperate forest in Japan and estimated the contribution of lianas to stand canopy transpiration. Based on a calibration measuring water uptake rates from cut‐stem ends, the actual sap flux ( F d ) in liana stems was several times greater than those estimated from the original calibration provided for the method. In the field, lianas showed an average of 2–4 times greater F d than trees throughout the year. Except for this difference, diurnal and seasonal patterns of relative changes of F d were similar in both groups. The whole‐plant transpiration ( Q t ) of sample plants was exponentially related to basal diameter for both lianas and trees; Q t of lianas increased more steeply with basal diameter than that of trees. By extrapolating the relationships between Q t and basal diameter to the inventory data of the study plot, we estimated that lianas contributed 12·8% to the annual stand canopy transpiration while comprising 2·3% of stand basal area, which probably reflected the top‐heavy architecture of lianas. Our results indicate that the contribution of lianas to forest water dynamics may be several times greater than their contribution to forest basal area. This implies that a slight increase of liana abundance might have greater effects on water dynamics and, through competitions with trees for limited water, the carbon sequestration capacity of forests than expected from the increase in basal area. This study underlines the necessity of evaluating the relative importance of lianas to forest water dynamics in forests world‐wide. A lay summary is available for this article. Abstract : Lay Summary